Stroke after coronary artery bypass grafting (CABG): A single center experience: Stroke incidence after CABG surgery - Ponce Parrado, Roxana; Saha, Sibu (Journal of Surgery and Medicine, 2026)
Background/Aim: Coronary artery bypass grafting (CABG) is among the ten most commonly performed surgical procedures in the United States. Despite advances in surgical techniques and perioperative care, stroke remains a serious complication, associated with significant morbidity and mortality. The aim of this study is to determine the incidence of stroke following CABG at a single institution, compare it with published rates from other centers, and identify common perioperative risk factors to support targeted, population specific prevention strategies. Methods: We conducted a retrospective chart review of 3,126 adult patients who underwent isolated coronary artery bypass grafting at our institution between 2016 and 2023. Data were collected on demographic variables, comorbidities, and perioperative factors. The incidence of postoperative stroke was determined, and comparative statistical analysis were performed to identify potential risk factors. Results: Postoperative stroke occurred in 1.3% of patients (41 of 3,126). The majority of affected individuals were white males aged 61 years or older. Common preoperative comorbidities included hypertension (95%), hyperlipidemia (87.8%), diabetes mellitus (75.6%), and a history of atrial fibrillation (26.7%). Postoperative respiratory failure was observed in 92.7% of stroke patients. Overall mortality in this group was 29.3%, with 24.2% of the casualties occurring within 30 days of surgery and an additional 4.9% within five years. Conclusions: The incidence of stroke following CABG at our institution (1.3%) falls within the range reported in the literature (1.2%–5.2%). Stroke was associated with longer hospital stays and increased mortality. Hypertension, diabetes mellitus, and hyperlipidemia emerged as the most prominent risk factors. These findings highlight the need for early risk stratification and proactive management of modifiable comorbidities to minimize stroke incidence in patients undergoing CABG.